1996
DOI: 10.1074/jbc.271.40.24576
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hepatocyte Growth Factor Stimulation of Keratinocyte Metalloproteinase Production

Abstract: Matrix metalloproteinases participate in normal physiologic processes; however, their overproduction has been associated with connective tissue destruction in a variety of pathological states. Migrating basal keratinocytes transiently express collagenase-1 during normal cutaneous reepithelialization. However, the overexpression of both collagenase-1 and stromelysin-1 has been associated with the pathogenesis of chronic nonhealing ulcers. Aberrant expression of metalloproteinases in inflammation is mediated, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 64 publications
2
69
2
Order By: Relevance
“…These events are likely to lead to increased cell motility, dissociation of cell-cell interaction and remodelling of cell-substrate interactions. In addition to these events, HGF induces urokinase-type plasminogen activator (uPA) expression (Pepper et al, 1992;Jeffers et al, 1996;Bennett et al, 1997;Date et al, 1998) and stimulates the production of matrix metalloproteinases (MMPs) (Dunsmore et al, 1996;Bennett et al, 1997;Date et al, 1998). Jeffers et al (1996) demonstrated that induction of the uPA proteolysis network by HGF is coupled to enhanced tumorigenicity and invasive and metastatic properties in certain tumour cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…These events are likely to lead to increased cell motility, dissociation of cell-cell interaction and remodelling of cell-substrate interactions. In addition to these events, HGF induces urokinase-type plasminogen activator (uPA) expression (Pepper et al, 1992;Jeffers et al, 1996;Bennett et al, 1997;Date et al, 1998) and stimulates the production of matrix metalloproteinases (MMPs) (Dunsmore et al, 1996;Bennett et al, 1997;Date et al, 1998). Jeffers et al (1996) demonstrated that induction of the uPA proteolysis network by HGF is coupled to enhanced tumorigenicity and invasive and metastatic properties in certain tumour cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed two groups of proteases, matrix metalloprotein-ases (12) and the serine protease urokinase (13,14), are upregulated by HGF/SF in different cell lines. Urokinase (15) converts plasminogen into plasmin, a serine protease with broad substrate specificity toward components of the extracellular matrix including laminin, vitronectin, and fibronectin (16 -18).…”
Section: Cells Expression Of An Expression Plasmid That Inhibits Dnamentioning
confidence: 99%
“…Later induction events correlate with HGF-induced epithelial and endothelial cell migration and morphogenesis, including increased production of transcription factor ETS1 (Fafeur et al, 1997), urokinase-type plasminogen activator (u-PA), and its receptor (Pepper et al, 1992), and the zinc ®nger protein slug (Savagner et al, 1997). The HGFstimulated proliferation and migration of keratinocytes that is thought to occur during wound healing Gohda et al, 1994;Watanabe et al, 1994;Nusrat et al, 1994;Sponsel et al, 1994), is accompanied by the induction of collagenase (matrix metalloproteinase 1; MMP-1; Dunsmore et al, 1996;Fafeur et al, 1997) and stromelysin-1 (MMP-3; Dunsmore et al, 1996). These induction events may be coordinated with the HGF-stimulated induction of plasminogen activator inhibitor-1, resulting in appropriate spatial and temporal inhibition of matrix proteolysis (Pepper et al, 1992;Wojta et al, 1994).…”
Section: Introductionmentioning
confidence: 99%